2023
DOI: 10.3390/life13020450
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Alpha-(α)-Solanine as a Natural Inhibitor of Fungus Causing Leaf Spot Disease in Strawberry

Abstract: Curvularia trifolii is an important pathogenic fungus that causes leaf spot disease in strawberry and other crops. Increased resistance in pathogenic fungi against chemical fungicides necessitates the search for biological alternatives to control plant fungal diseases. The present study aimed to perform transcriptome and metabolome analysis of C. trifolii fungi. We evaluated the potential of an alkaloid, namely alpha (α)-solanine, to inhibit the growth of Curvularia under in vitro conditions. Furthermore, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…PGA could inhibit the colony growth of pathogenic fungi such as A. solani ( Wolters et al, 2023 ) and P. brasiliense ( Joshi et al, 2021 ). PGA inhibited the mycelial growth rate and spore germination of C. trifolii ( Xu et al, 2023 ), and inhibited the growth of F. sulphureum by inhibiting ROS metabolism and destroying cell membrane ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGA could inhibit the colony growth of pathogenic fungi such as A. solani ( Wolters et al, 2023 ) and P. brasiliense ( Joshi et al, 2021 ). PGA inhibited the mycelial growth rate and spore germination of C. trifolii ( Xu et al, 2023 ), and inhibited the growth of F. sulphureum by inhibiting ROS metabolism and destroying cell membrane ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PGA can inhibit the growth and development of Botrytis cinerea ( Sun et al, 2014 ), Pectobacterium carotovorum ( Rocha et al, 2015 ), Alternaria alternata and Pyrenophora tritici-repentis ( Sanchez-Maldonado et al, 2016 ), Phytophthora infestans ( Dahlin et al, 2017 ). PGA could inhibit the spore germination of Curvularia trifolii ( Xu et al, 2023 ), reduce the virulence of Pectobacterium brasiliense ( Joshi et al, 2021 ), inhibit the active oxygen metabolism process of F. sulphureum to exert antifungal effect ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PGA can inhibit the growth of Pectobacterium carotovorum as well as weaken the vitality of Pectobacterium bacterial and reduce its pathogenicity [8,9]. PGA inhibited the mycelium growth of Pyrenophora teres, Alternaria alternata, and Phytophthora infestans and the spore germination of Curvularia trifolii [10][11][12], and was able to kill part of the mycelium of Fusarium sulphureum and inhibit its growth [13].…”
Section: Introductionmentioning
confidence: 99%